Cytotoxic effect of Luffa cylindrica leaf extract on MCF-7 cell lines - Arshad, Hanzla; Saleem, Mohammad (Bangladesh Journal of Pharmacology, 2025)
This study investigated the cytotoxic effect of Luffa cylindrica leaf aqueous ethanolic extract on breast cancer cell lines MCF-7 and the normal epithelial cell line MCF-10A. Phytochemical screening and DPPH assays confirmed the presence of antioxidant compounds. MTT showed a dose-dependent reduction in cancer cell viability (p<0.05), with minimal effects on MCF-10A. Doxorubicin, in contrast, was toxic to MCF-7 cell lines. Apoptotic cell death induced by the extract was verified through morphological analysis, annexin V-FITC binding, and Hoechst/propidium staining. The extract significantly reduced reactive oxygen species (ROS) and delayed cell migration, as observed in the scratch assay. Overall, L. cylindrica demonstrated selective cyto-toxicity, antioxidant potential, and anti-metastatic properties, supporting its potential as a promising natural candidate for breast cancer treatment.